2014
DOI: 10.1089/end.2013.0630
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative, Pathologic, and Early Continence Outcomes Comparing Three-Dimensional and Two-Dimensional Display Systems for Laparoscopic Radical Prostatectomy—A Retrospective, Single-Surgeon Study

Abstract: Laparoscopic RP aided by a new-generation 3D display system is associated with shorter operative times, reduced blood loss, and higher early continence rates in comparison with that aided by a 2D display system. In particular when considering economic issues, 3D laparoscopic RP may represent an acceptable alternative to robot-assisted laparoscopic RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…One study reported that 3D visualization reduced operation duration from 284 minutes using the 2D HD system to 225 minutes in laparoscopic liver resection, with no significant difference in blood loss . Aykan et al reported a shorter operating duration and reduced blood loss in the 3D HD group in a cohort of patients who underwent laparoscopic radical prostatectomy . Bagan et al compared 3D HD thoracoscopic surgery with 2D HD lobectomy and reported that the 3D HD system significantly reduced surgical duration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported that 3D visualization reduced operation duration from 284 minutes using the 2D HD system to 225 minutes in laparoscopic liver resection, with no significant difference in blood loss . Aykan et al reported a shorter operating duration and reduced blood loss in the 3D HD group in a cohort of patients who underwent laparoscopic radical prostatectomy . Bagan et al compared 3D HD thoracoscopic surgery with 2D HD lobectomy and reported that the 3D HD system significantly reduced surgical duration .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the advantages of 3D HD over conventional 2D HD in terms of improving surgeon performance in standardized basic skills tasks . More recent studies have suggested a possible advantage of these new‐generation 3D HD systems during laparoscopy …”
Section: Introductionmentioning
confidence: 99%
“…Specifically to urology, Aykasan et al recently reported a comparative outcome analysis of laparoscopic radical prostatectomy by using 3D vs 2D imaging. 16 They found that the 3D procedure was faster (mean operative time, 131 vs 190 minutes for 2D; P <.001), and this was mostly related to the performance of urethra-vesical anastomosis. Moreover, they obtained a higher early recovery of continence with 3D patients (50% vs 25%; P ¼ .02).…”
Section: Commentmentioning
confidence: 96%
“…20 For other surgical procedures, the value of 3D vision has been frequently described. 9,14,21,22 The addition of the third dimension in endoscopy entails a natural view on the operating field, which facilitates orientation in space and identification of dissection planes. In addition, the flexible camera tip of the new-generation 3D systems contributes to a more intuitive way of tissue preparation by allowing a broader range of motion of up to 100°instead of the conventional 30°.…”
Section: Discussionmentioning
confidence: 99%